Evaluation of stent placement and outcomes with optical coherence tomography. (August 2010) - Shinke, Toshiro; Shite, Junya
Optical coherence tomography (OCT) is an imaging modality based on fiberoptic technology. OCT imaging systems use optical imaging catheters that emit near-infrared light to produce high resolution, real-time images. The frequencies and bandwidths of infrared light are far higher than medical ultrasound signals, resulting in greatly increased image resolution, which is approximately ten-times higher than that of intravascular ultrasound. Compared with conventional imaging modalities, OCT is superior for the evaluation of vulnerable plaque features, which may be associated with a higher risk of peri-interventional myocardial infarction, such as plaque rupture, thrombus, thin-capped fibroatheroma and macrophages within the fibrous caps. OCT can clearly visualize stent malapposition and tissue prolapse after stent deployment, as well as neointimal hyperplasia and persistent thrombus at follow-up. OCT provides new insight into the assessment and treatment of coronary artery disease with stent placement.